2020
DOI: 10.3390/app10072443
|View full text |Cite
|
Sign up to set email alerts
|

Research on a Nonlinear Dynamic Incipient Fault Detection Method for Rolling Bearings

Abstract: The incipient fault detection technology of rolling bearings is the key to ensure its normal operation and is of great significance for most industrial processes. However, the vibration signals of rolling bearings are a set of time series with non-linear and timing correlation, and weak incipient fault characteristics of rolling bearings bring about obstructions for the fault detection. This paper proposes a nonlinear dynamic incipient fault detection method for rolling bearings to solve these problems. The ke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…On the basis of the above model, Shi et al proposed a general form of nonlinear model, namely, the state-dependent model. In the past two decades, studies on the combination of this model and the RB Qiusheng meridian network have also been developed and applied to relevant engineering elds [5]. Ren et al proposed the functional cocientar model, which is also a special case of the state-dependent model [6].…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of the above model, Shi et al proposed a general form of nonlinear model, namely, the state-dependent model. In the past two decades, studies on the combination of this model and the RB Qiusheng meridian network have also been developed and applied to relevant engineering elds [5]. Ren et al proposed the functional cocientar model, which is also a special case of the state-dependent model [6].…”
Section: Introductionmentioning
confidence: 99%
“…Through application of Gabor wavelet coefficient squared envelope spectrum analysis method, Wang et al [47] detected the incipient fault occurrence at the No.533 data file. Using an improved empirical mode decomposition method to extract the incipient fault characteristic frequency, Fan et al [7] detected the incipient fault occurrence at the No.532 data file.…”
Section: A Laboratory Data Validationmentioning
confidence: 99%
“…In [4][5][6], an IFD method based on prior physical knowledge, which requires the establishment of an accurate physical model, has been investigated. However, the internal stress and other physical quantities of the running rolling bearings are relatively difficult to characterize, which often results in poor model generalization [7]. An IFD rolling bearings method based on the analysis of fault characteristic frequencies is established in [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…The model was created by identifying patterns in the distribution of the experimental data and their interrelationships, based on non-linear regression analysis [27,28]. The analysis of the experimental data showed that the rate of change of a variable is proportional to its actual value.…”
Section: Introductionmentioning
confidence: 99%